PERBANDINGAN EFEKTIVITAS DAYA HAMBAT DADIH DENGAN YOGURT TERHADAP PERTUMBUHAN BAKTERI STREPTOCOCCUS MUTAN - Indah Maydila Sandi; Hafni Bachtiar; Hidayati Hidayati (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2015)
Dadih and yoghurt are functional food products that gives health benefits because it contains probiotic bacteria. Lactic acid bacteria in probiotic foods can produce antimicrobial lsubstrates, organicacids, ethanol, hydrogenperoxide, andbacteriocins. Streptococcus mutans is a gram-positive coccibacteria that became a major factor of caries. The aim of this reseacrh is to determine the effective ness differences between dadih and yoghurt to inhibit growth of Streptococcus mutans. This research is a laboratory experimental with well agar diffusion method on blood agar as a medium to see a inhibition zone by antimicrobial activity. This research used 36 well-agar which contains 50 μl of dadih and 50 μl yoghurt respectively. Result showed that mean rank of dadih’s inhibition zone is 12,75 mean while yoghurt’s inhibition zone is 24,25. Mann-Whitney test showed that p value=0,001. There was a significant inhibition effect between dadih and yoghurt on growth of Streptococcus mutans.It concluded that dadih and yoghurt have an antimicrobial effect to inhibit growth of Streptococcus mutans. Daily consumption of probiotic foods gives benefit for oral health.